Data Centric Peer-to-Peer Communication in Power Grids - Gerdes, Christoph; Eger, Kolja; Müller, Jörg (Electronic Communications of the EASST, 2009)
We study the use of peer-to-peer based declarative data management to enable efficient monitoring and control of power transmission and distribution networks.We propose methods and an architecture for data centric communication in power networks; a proof-of-concept decentralized communication infrastructure is presented that uses and advances state of the art peer-to-peer and distributed data management protocols to provide real time access to network state information. We propose methods for adaptive network reconfiguration and self-repair mechanismsto handle fault situations. To efficiently handle complex queries, we present a centralized metadata index, and propose a query language and execution method that allows us to handle high volume data streams in-network.